LEGAL PROTECTION OF CREDITORS AND DEBTORS THROUGH NOTARIAL DEEDS IN BANKING CREDIT AGREEMENTS - Hendrik Reba, William; Simanjuntak, Josner; Edbert Reba, Jeremy (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
Bank credit plays a vital role in economic development, but is often associated with legal risks such as default, the use of unilateral clauses, and disputes over collateral enforcement. Both creditors and debtors require strong legal protection to ensure fairness and certainty in credit agreements. This article examines the role of notarial deeds as an instrument of legal protection for both parties in bank credit transactions. This research uses a normative legal research method with statutory, conceptual, and comparative approaches. The primary legal materials include the Civil Code (KUHPerdata), the Banking Law, and the Notary Law (Law No. 2 of 2014). A comparative analysis was also conducted with the Dutch and German legal systems to highlight international best practices. The results show that notarial deeds provide both preventative and repressive legal protection. For creditors, notarial deeds guarantee legal certainty, enforceable powers, and protect against the risk of default. For debtors, notarial deeds serve to prevent detrimental clauses, ensure transparency of obligations, and strengthen equality in contracts. Furthermore, the notary's preventive role strengthens contractual fairness by protecting both parties from potential future disputes. The conclusion of this study confirms that a notarial deed is not merely an administrative requirement, but rather a legal protection instrument that balances the interests of creditors and debtors. Optimizing this role requires increased notary professionalism, regulatory harmonization, and stricter oversight.